Gender-sensitive language in textbooks: Examples of good practice - Stevanović Marjana M. (Reči (Beograd), 2023)
Since the first national strategy (2009) aimed at eliminating discrimination against women in all areas in the domain of public institutions, including education, publishing houses which publish school textbooks have started to implement gendersensitive language into their materials. Today, more than ten years later, gender-sensitive language practice has already been introduced into many textbooks for elementary and secondary schools. However, it still has not been approved by the Board for Standardization of the Serbian Language. This paper presents examples of the use of gender-sensitive language collected from 13 elementary school textbooks published in the period 2019-2022 and appproved by the Ministry of Education, Science and Technological Development. Based on those examples, which largely implemented the first proposals for the use of gender-sensitive language formulated by Svenka Savić (Savić et al, 2010), it is possible to create new recommendations for a more consistent use of language that would correspond to the requirements of legal regulations in the field of gender equality as well as to the language norm.